Impacts of immigrants to gdp in malaysia: manufacturing, construction, services and agriculture - Heizlyn Amyneina Binti Hamza; Estro Dariatno Sihaloho (Faculty of Economics and Business Mulawarman University, 2019)
International migration had occurred since World War ΙΙ and this global phenomenon keep growing in number especially in South East Asia countries. International migration usually occurred as a labor migration. Father of Economics, Adam Smith, describes labor migration as due to the imbalance in the labor market at different locations. Malaysia is a developing country in South East Asia that received thousands even millions of immigrants from Indonesia, Nepal, Bangladesh, Thailand, Philippines and Myanmar. These immigrants are filling the gap as low-skilled labors in sectors such as construction, manufacturing, and industrial. This paper aims to study and analyses the impacts of immigrants in different home countries to the host country, Malaysia in the context of gross domestic product (GDP). Does the migrants from different home countries giving impact to the GDP of Malaysia? In achieving the aim of the paper, authors used total GDP of Malaysia as dependent variable and number of immigrants in manufacturing, construction, service and agriculture as output. Data in this paper contained the number of immigrants in Bangladesh, Indonesia, Nepal and Myanmar segregated by their sector from 2013-2016. Authors used STATA 12 to regress the panel data and from the regression, authors obtained the significant effect of immigrants of manufacturing, services, and agriculture on GDP of Malaysia. Meanwhile, immigrants of construction and housemaid have insignificant effect on GDP of Malaysia. Hence, hiring immigrants from Bangladesh, Indonesia, Nepal and Myanmar will only benefits Malaysia if the immigrants work on sectors such as services and agriculture.